Evaluasi lanskap jalur sepeda di Kawasan Niti Mandala Kota Denpasar, Provinsi Bali - Ashari, Yogi; Asmiyati, I Gusti Agung Ayu Rai; Sugianthara, Anak Agung Gede (Jurnal Arsitektur Lansekap, 2022)
The activity of cycling tends to reduce in Indonesia nowadays. It may be caused by the lack of adequate space and facility provided as well as the low maintenance of the existing bicycle facilities. This phenomenon can be seen in the area of Niti Mandala, Denpasar, Bali which already being provided by bicycle lane. This study aims to identify the existing condition of bicycle paths and to evaluate the landscape bicycle path in the Niti Mandala. This study used surveys and data collection techniques through observation, interviews, and literature study. An analysis of SWOT (Strength, Weaknesses, Opportunity, Threat) was used to further quantify and improve the quality of the collected data. The main strategy analysis resulted improvements of the existing bicycle line was mainly important. It was also suggested routinely remark the bicycle line and the provision of the bike on bus program to support the sustainability of the bicycle landscape and the go green program of Denpasar City.